The Effect of the Search, Solve, Create, and Share (SSCS) Learning Model on Students’ Scientific Reasoning Ability - Putri, Atik Indriati; Lengkana, Dewi; Yolida, Berti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to determine the effect of using the Search, Solve, Create, and Share (SSCS) learning model on the scientific reasoning abilities of 12th-grade students in the topic of heredity. The sample consisted of 62 students from two classes, selected using purposive sampling. This research employed a quasi-experimental method with a non-equivalent pretest-post-test control group design. The data were analysed using an independent sample t-test at a 5% significance level. The results showed that the application of the SSCS model had a significant effect on improving students’ scientific reasoning, with a sig. (2-tailed) value of 0.000 < 0.05. The average N-Gain in the experimental class was 0.46, which falls under the medium category. The highest increase occurred in the probabilistic reasoning aspect (N-Gain = 0.42), while the lowest increase was in the combinatorial reasoning aspect (N-Gain = 0.36), both classified as medium. The effect size of the SSCS model on scientific reasoning was 1.47, which is categorized as large. Based on the questionnaire results, 78.43% of students agreed that the SSCS learning model made them more active in the learning process and helped them achieve a better understanding of heredity material. It can be concluded that the application of the SSCS model positively influences the improvement of students’ scientific reasoning skills and is well accepted by the students.Keywords: Search, Solve, Create, and Share Model; Scientific Reasoning